Performance Evaluation of N-Body Simulations on AWS with StarPU, OpenMP and MPI Runtime Systems - Vanz, Nicolas; Munhoz, Vanderlei; Castro, Márcio (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2025: Anais do XXVI Simpósio em Sistemas Computacionais de Alto DesempenhoDO - 10.5753/sscad.2025.15831, 2025)
Cloud Computing provides a cost-effective option for High Performance Computing (HPC) workloads, but brings new challenges. This study evaluates StarPU, a task-based runtime for heterogeneous architectures, in cloud environments by running an N-Body simulation under different cluster configurations and comparing it with traditional HPC runtime systems (OpenMP and MPI). Results show that StarPU excels in single-node setups, especially with GPU acceleration, while scalability varies, struggling with CPU-intensive workloads but performing well in hybrid and GPU-only scenarios. These insights highlight the need for careful infrastructure selection and architectural strategies to ensure good performance in cloud-based HPC.